2016
DOI: 10.1051/shsconf/20163101004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of obesity awareness stage of secondary school students

Abstract: Abstract. In this study, it was aimed to investigate obesity awareness stage of 8th class students in secondary school who entered TEOG examination organized by Ministry of National Education in terms of different variables. The research was carried out with 268 male and 232 female students. Moreover, "Obesity Awareness Scale" developed by Allen (2011) and "and Turkish validity and reliability of which was performed by Kafkas&Özen (2014) as well as Personal Information Form" were used. In the analysis of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Finally, no statistically significant relationship was found between the students' obesity awareness total score, obesity awareness, nutrition awareness and physical activity awareness sub-dimension scores, and the BMI of the students. This is supported by research findings that of Atlı, Özkan and Uyar (2016) that examining the levels of secondary school students obesity awareness. Researchers revealed that there is no statistically significant difference between the obesity awareness total scores and obesity awareness, nutrition awareness and physical activity awareness sub-dimension scores of young female and male students.…”
Section: Discussionmentioning
confidence: 56%
“…Finally, no statistically significant relationship was found between the students' obesity awareness total score, obesity awareness, nutrition awareness and physical activity awareness sub-dimension scores, and the BMI of the students. This is supported by research findings that of Atlı, Özkan and Uyar (2016) that examining the levels of secondary school students obesity awareness. Researchers revealed that there is no statistically significant difference between the obesity awareness total scores and obesity awareness, nutrition awareness and physical activity awareness sub-dimension scores of young female and male students.…”
Section: Discussionmentioning
confidence: 56%
“…Kara (2017) states that there is asignificant difference between students' OAS sub-dimensions and PAQC scores based on their parents' educational levels. Atli et al (2016) observed no statistical significance between the total score and the sub-dimensions of parents' education status, reading books, watching television, fast food eating habits, and obesity awareness in their study.…”
Section: Discussionmentioning
confidence: 73%
“…The significant difference for OAS was caused by higher mean score of boys studying in the private school. Atlı et al (14) found in their study that girls had higher subscales and scale mean scores compared to boys but there was no significant difference. This difference in the study suggested that boys studying in the private school had high obesity awareness.…”
Section: Discussionmentioning
confidence: 84%
“…Washington et al (13) investigated the effect of ecological factors and family in normal and overweight children in preschool period and found that they were effective. In their study, Atlı et al (14) investigated obesity awareness of secondary school students and they found a significant difference between body mass index and gender. In their study, Sözen and Bebek (15) examined the obesity awareness of university students and found that women had more obesity awareness than men.…”
Section: Introductionmentioning
confidence: 99%